A study on how the delayed claims from buyer’s loan can affect Bulatan Mekar Sdn Bhd / Anis Aliya Mohd Yusoff - Mohd Yusoff, Anis Aliya (Faculty of Business and Management, 2009)
This study provides an analysis regarding to the delayed claims from buyer’s loan. The purpose of this study is to analyze how this delayed claim can affect Bulatan Mekar Sdn Bhd. This study is also to identify what are the factors that contribute in this delayed claim. In Bulatan Mekar Sdn Bhd, claim is important because it is as a payment to finance their construction projects. Besides that, to understand what is claim I also study the procedure of claim in this company. These studies also try to answer what are the effects that may arise in the delayed claim. In order to analyze the issues, the data have been collected from primary and also secondary sources. Data and information had been collected from the article, internet, journals and annual report and as well as from interviewing the executives in Bulatan Mekar Sdn Bhd.